2009
DOI: 10.1002/lsm.20855
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level laser therapy as a non‐invasive approach for body contouring: A randomized, controlled study

Abstract: These data suggest that low-level laser therapy can reduce overall circumference measurements of specifically treated regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 58 publications
5
67
0
2
Order By: Relevance
“…In that study, a reduction of approximately 2.0 cm in the treatment area (abdomen, thighs, or flanks) was achieved within 2 weeks after a single treatment and lasted for 12 weeks [18]. However, this reduction was lower than that of other noninvasive body-contouring techniques such as radiofrequency, low-level laser therapy, and HIFU, which reported reductions of [3.5 cm [27][28][29].…”
Section: Discussionmentioning
confidence: 79%
“…In that study, a reduction of approximately 2.0 cm in the treatment area (abdomen, thighs, or flanks) was achieved within 2 weeks after a single treatment and lasted for 12 weeks [18]. However, this reduction was lower than that of other noninvasive body-contouring techniques such as radiofrequency, low-level laser therapy, and HIFU, which reported reductions of [3.5 cm [27][28][29].…”
Section: Discussionmentioning
confidence: 79%
“…Maximum fat reduction was reported across the waist (2.66 cm). However, two weeks after the last treatment session, a 7.8-mm increase in circumferences was seen in three treated zones (62). In another clinical study, Jackson et al reported that treating 689 subjects with LLLT (12 treatment sessions within 14 days) leads to 13.13-cm circumferential reduction in waist, hips, thighs, arms, knees, neck and chest (63).…”
Section: Resultsmentioning
confidence: 99%
“…LLLT has been separately reviewed as a modality 53 and was investigated via Zerona (Erchonia) [54][55][56][57][58][59][60] 56,[59][60] . Six of the seven studies published on LLLT for body contouring used the Zerona device, with treatments 3 times per week for 2 weeks and results first noted at 1 week 59 .…”
Section: Llltmentioning
confidence: 99%